User-centered design of central venous access device documentation. Issue 1 (4th March 2022) - Kandaswamy, Swaminathan; Gill, Anne; Wood, Shellie; Mckay, Leah; Hike, Jessica; Popkin, Melissa; Ray, Edwin; Maude, Heather; Johnston, Crawford; White, Tenia; Orenstein, Evan
Abstract: Objective: Safe care of central venous access devices (CVAD) requires clinicians be able to identify key CVAD properties from insertion until safe removal. Our objective was to design and evaluate interfaces to improve CVAD documentation quality and information retrieval. Materials and Methods: We applied user-centered design (UCD) to CVAD property documentation interfaces. We measured expert agreement and front-line clinician accuracy in retrieving key properties in CVADs documented pre- and postimplementation. Results: The new approach (1) optimized searches for line types, (2) enabled discrete entry of key properties which propagated to the display name, and (3) facilitated error correction by experts. Expert agreement on key CVAD properties improved from 42% to 83% ( P  < 0.01). Frontline nurses' perception of key CVAD properties improved from 31% to 86% ( P  < 0.01). Ease of use scores improved from 15/100 to 80/100 ( P  < 0.01). Conclusions: UCD significantly improved data quality and nurse perception of CVAD properties to guide subsequent care. Lay Summary: Central venous access devices (CVADs) are inserted into the deep central veins to enable safe administration of fluids, medications, and other therapies to the bloodstream. Safe care of CVAD requires clinicians be able to identify key CVAD properties. We report the design and implementation of a new interface for CVAD documentation in the electronic health record using a user-centered design (UCD) approach. The new design optimized search for line types, enabled discrete entry of key properties that propagated to display names, and facilitated error correction by experts. Our evaluation found that the new approach was efficient, easy to use, and it significantly improved the quality of CVAD documentation and provider awareness of CVAD properties.